ANALISIS KARAKTER DISIPLIN DAN PEDULI LINGKUNGAN PESERTA DIDIK KELAS V SEKOLAH DASAR - Hilmi, Ajeng Zakiah; Nugraha, Fajar; Wakih, Agus Ahmad (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The character of students must be formed from an early age, because character has an important role in the formation of a generation that is able to live independently with correct principles and can be accounted for. Discipline and caring for the environment are characters that every elementary school student must have. The purpose of this study was to analyze the character of discipline and care for the environment in grade 5 elementary school students in Tasikmalaya Regency. The research method used is descriptive qualitative with a phenomenological approach. The samples in this study were 4 male students and 4 female students who were observed through observation. Data processing techniques through 4 stages, namely data collection, data reduction, data presentation and conclusions. The results of this study state that there are differences in the character of discipline and care for the environment between male and female students who are influenced by character education carried out by schools, as well as several other factors including gender roles, brain differences, gender socialization, gender communication and empathy. However, these factors cannot be generalized broadly, there are other factors that can affect the character of discipline and care for the environment of students.